PENGARUH PROFITABILITAS TERHADAP KEBIJAKAN UTANG MELALUI KEBIJAKAN DEVIDEN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2014) - Puspa Devi Maharani; Lulu Nurul Istanti; Fadia Zen (Jurnal Akuntansi Aktual, 2017)
The study aims to determine the effect of profitability directly and indirectly on debt policy through dividend policy. The population of the study were 152 manufacturing companies listed on the Indonesia Stock Exchange in 2012-2013. The samples of the study were 27 companies. This research used quantitative method and path analytical approach using SPSS 16.0 version. The results showed that profitability has positive direct effect on the debt policy, profitability has positive effect on dividend policy, dividend policies has negatively effect on debt policy, profitability has effect on debt policy through dividend policy in the manufacturing companies.Keywords:debt policy, profitability, dividend policy